Perceptions of reflecting team practice in family therapy - Buchanan, Megan Rae (My University, 2014)
This research investigates the claims made by proponents of reflecting team practice in family therapy. The study explores the relationship between these claims and the experience of families in the reflecting team approach. Five families were involved in a qualitative study. Questionnaires and interviews were used as the means to gather data. The data was analysed by content analysis. This analysis yielded codes and themes associated with the experience of the reflecting team approach. The data analysis generated two story lines - a positive and negative storyline. While the positive storyline confirmed claims, the negative story line negated certain of the proponent's claims. What appears to have been negative for these families was not reflecting team practice per se but the manner in which the reflections were offered by the team.However, this may also suggest that reflecting team practice is perhaps more appropriate for some families, or for some family problems, than for others.